Comparison of isokinetic force of the internal and external rotators of the shoulders between swimmers of alternate and simultaneous techniques - Santos, Y. S.; Carneiro, N.; Franken, M.; de Jesus, K.; de Jesus, K.; Medeiros, A. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to compare the peak torque and the strength ratio between the external and internal swimmers` right and left shoulder rotators between alternate and simultaneous swimming techniques. Sixteen competitive swimmers (3 females and 13 males) were divided equally into two groups, alternate and simultaneous swimming techniques. The experimental protocol consisted of three maximum concentric repetitions of internal rotation and external rotation of the shoulder at an angular velocity of 60°/s and twenty repetitions at a velocity of 180°/s, with a two minutes interval between speeds and four minutes in the change of laterality of the upper limbs on a Biodex isokinetic dynamometer (Biodex System 4.0, Biodex Corp., Shirley, NY, EUA).The peak torque and the strength ratio between the external and internal swimmers` right and left shoulder rotators were measured. No difference was obtained between swimming techniques for peak torque and the strength ratio between the external and internal swimmers` right and left shoulder rotators (p > 0.05), except for the right shoulder internal rotation at 180º/s (alternate: 44.13 ± 11.58; simultaneous: 56.25 ± 8.83; p < 0.05). Based on our results, peak torque and the strength ratio between the external and internal swimmers` right and left shoulder rotators do not seem to be influenced by the athlete's predominant swimming technique, with alternate (front crawl and backstroke) or simultaneous (breast and butterfly) strokes. The main findings of this study show that the balance relationships between the ER/IR rotators of the shoulders do not seem to be differentiated by the alternate and simultaneous swimming techniques. However, observing only the PT/IR at a speed of 180°/s of the right shoulders, there was a significant difference between the groups and, therefore, the ER/IR balance ratio was at the maximum limit of normality. Regardless of the specialization of the swimming technique, that is, alternate or simultaneous, swimmers can present imbalances in the internal and external rotators of the shoulders, which reveal the need for compensatory strength training focused on the rotator muscles of the shoulder.